Penguatan Profil Pelajar Pancasila melalui Pembelajaran IPS di SD/MI - Fatmawati, Ludya; Alma Pratiwi Husain (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The younger generation in Indonesia faces significant challenges in the form of an identity crisis and moral degradation due to the increasingly strong influence of other cultures in the era of globalization and the fifth industrial revolution. A pragmatic culture that does not always align with national identity puts pressure on Pancasila principles such as belief in God, humanity, unity, democracy, and social justice. As a result, character education integrated into social studies instruction serves as a tactical tool to reintroduce these fundamental principles to students from an early age. This study, using qualitative methodology and a descriptive design, found that contextualized and project-based social studies instruction not only enhances students' understanding of Pancasila values ​​but also fosters the growth of critical thinking skills, social empathy, reflective attitudes, and a spirit of cooperation. When combined with digital tools like Canva, Taman Siswa's teachings—niteni, niroake, and nambahi—have proven successful in developing students' creativity and enhancing their purpose and enjoyment in learning.